Caracterização estrutural e medidas de magnetização em (Dy,Y)3Fe3Al2O12 e Lan+1NinO3n+1 (n= 1, 2, 3) Lan+1NinO3n+1 (n = 1, 2, 3) - Silva, Cláudia Adriana da (2016)
This study describes two families of transition metal oxides (OMT). Because of its potential and diversity of physical properties, the OMT are promising candidates for technological applications. In contrast, physically understand the complex relationship of these properties has been the main challenge of the research in this area. One of the families that was studied in this work are composed of Ruddlesden Popper type (RP), nickel base, of formula Lan+1NinO3n+1. The RP oxides have become more popular in the decade of 80, when it was discovered that a compound of this family, the La2CuO4− can become superconductive when appropriately doped. Another important property associated with the RP oxides is the colossal magnetoresistance, observed in the manganese-based compounds, such as Ca3−xLaxMn2O7. Another family of OMT studied in this work are the compounds garnets type of formula R3Fe5O12 (Where R is rare earth element or Y). This family is known to be rich in physical properties, especially magnetic, The magnetism of these compounds is associated mainly with the ferrimagnetic interaction between ions of Fe3+ in octahedral and tetrahedral coordination. The magnetic moment resulting from interactions of the Fe3+ can orient yourself antiferromagnetic with the network ion R, if it is a rare earth magnetic. A property that has been strongly investigated in compounds garnets is the magnetocaloric effect (EMC). This effect, which tracks the magnetic transitions, is more relevant and meaningful in compounds that are promising candidates for use in magnetic refrigeration. To investigate some of the physical properties of these systems were synthesized compounds (Dy, Y)3Fe3Al2O12 and Lan+1(Ni1−xZnx)nO3n+1 (n = 1, 2, 3 e 0 ≤ x ≤ 0.5). To synthesize the samples used two methods, combustion reaction (RC) and coprecipitation (CP). Both methods have proven effective for obtaining samples with the desired phase. The technique of X-ray diffraction, together with the Rieteveld refinement method was used to extract crystallographic information of the synthesized compounds. Morphological information of samples, such as size, shape and distribution of particles were investigated by the technique of scanning electron microscopy. The micrographs show that regardless of the synthesis method, the particle shape is not well defined and the size distribution is inhomogeneous. Some samples of garnets type, synthesized by CP, have particle size in the nanoscale. Some compounds were characterized by electrical resistivity measurements as a function of temperature, where it was found that the series La2Ni1−xZnxO4 it has semiconducting properties in the temperature range from 10 KM to 300 K. The magnetic properties were investigated by magnetization measurements as a function of temperature and magnetic field, where it was found that the magnetism of both systems is affected by the inclusion of non-magnetic ions. EMC was investigated in two samples of garnets type, the data were obtained from the magnetization as a function of temperature and it was found that the aluminum insert in the structure, replacing the iron, decreased temperature magnetic transition, but also reduced the intensity EMC.